AB0020 B-lymphocyte function is altered by protease activated receptor-1. (23rd January 2014) - McKelvey, K.; Jackson, C.; Xue, M.
Abstract : Background: Protease-activated receptors (PARs) play an important role in most inflammatory and immune cell types, however, they have not been studied in B-lymphocytes. Objectives: We sought to determine whether PAR1 or PAR2 were expressed by B-lymphocytes and if so, to determine their effect on cell proliferation, cytokine and antibody production. Methods: Human "immature" B-cell lines Ramos and Raji, and "mature" EBV-LCL1 cells, and murine wildtype, PAR1 or PAR2 knock-out (KO) splenic B-lymphocytes were used. Cells were treated with 10 µM PAR antagonists or NFkB, ERK and p38 inhibitors, and assessed for cell proliferation by MTT assay and protein expression by ELISA, western blot and flow cytometry. Results: Both PAR1 and PAR2 were expressed by all three cell lines. PAR1 antagonist increased IL-6, IL-10 and IgG in centroblast-like Ramos cells (p<0.01); IL-6 and IL-1β in centrocyte-like Raji cells (26- and 24-fold, p<0.01); and IgG in peripheral blood-derived EBV-LCL1 cells (3.1-fold, p<0.01). PAR2 antagonist decreased IL-10 and IgM in Ramos (both 0.85-fold, p<0.05); IL-1β in Raji (0.75-fold, p=0.03); and IgG in EBV-LCL1 (0.83-fold, p<0.05). PAR2 antagonist modestly increased Ramos and EBV-LCL1 cell proliferation (p<0.05), but had no effect on Raji. PAR2 KO cell proliferation did not differ from wild type. In contrast, cell proliferation was inhibited ∼21-fold by PAR1 antagonist in all B-lymphocyte types and 36-fold in PAR1 KO cells (p<0.001). B-lymphocyte PAR1 signalling was mediated via NFκB and ERK, and PAR2 signalling via NFκB, ERK and p38. Conclusions: PAR1 and PAR2 are expressed by B-lymphocytes and, exert differential effects on cell proliferation and cytokine and antibody secretion. Disclosure of Interest: None Declared